‘Giving the right service to different people’: revisiting police legitimacy in the Covid-19 era - Charman, Sarah (Policing and society, 2023)
The suspension of certain civil liberties and the extension of police powers to combat the spread of the Covid-19 pandemic has provoked concerns about the longer-term implications of the pandemic on police legitimacy. Drawing upon pathways to police legitimacy identified within the literature, this paper examines police officers’ perceptions of the impacts on, and potential challenges to, police legitimacy arising from the pandemic. Qualitative interviews, video diaries and focus groups were conducted with police officers in one police force area in England, captured over a five month period in winter 2020/21. The experience of policing Covid-19 left many police officers concerned about the possible consequences for the relationship with the public. The paper cautions that any gains in public perceptions of procedural justice through using enforcement measures only as a last resort, may be offset by losses in other pathways to legitimacy. Expectations of enforcement and increased visibility plus prolonged changes to deployment practices have all heightened a focus on the more instrumental aspects of police legitimacy. Concerns were also voiced that the policing of Covid-19 has accentuated divisions in society, exacerbating the sense of multiple publics to police, with different and often competing expectations of – and beliefs about – the police. Enforcement falling more heavily within some groups and locations risks exacerbating long-standing concerns about distributive fairness. As agents of social control with unique powers to exercise force and compulsion, the pandemic will require the police to exercise continued vigilance on the means by which public consent and support are sustained.